A NOTE ON A POSSIBLE ALLERGIC FACTOR IN ALTITUDE SICKNESS - BAKER, JULIA (MEXICO, DF, MEX, 1952)
From the records of a random sample from private practice of 500 individuals in Mexico City, fifteen years of age and under, about 50 per cent were found to be frankly allergic. Of the five hundred, 167 had either severe hives, urticarial rashes or eczema
J LAB CLIN MED
Keywords: NOTE, ALLERGIC, ALTITUDE, SICKNESS; CIENCIAS MEDICAS; PATOLOGIA; ALERGIAS